Understanding the "Fear of Missing Out" (FOMO) Phenomenon Among Retail Investors in the Indonesian Capital Market: A Literature Review - Laraga, Abdul Gani (Journal of Applied Accounting and Taxation, 2025)
The study examining the Fear of Missing Out (FOMO) phenomenon among Indonesian retail investors found that it is a significant driver of impulsive and herding investment behaviors. Using a qualitative literature review of studies from 2019 to 2025, the research identified several key characteristics and triggers of FOMO. The study revealed that FOMO is often characterized by investors abandoning fundamental analysis in favor of following the crowd. Its primary triggers are the rapid spread of information on social media, the bandwagon effect, and low financial literacy. These factors collectively lead to suboptimal decisions, increased risk, and psychological stress for investors. The research concludes that mitigating FOMO is crucial for a stable capital market. Effective strategies include improving financial literacy, encouraging long-term investment planning, and promoting self-discipline. These educational and regulatory measures are essential to fostering a more rational investment environment.